Influencer Marketing Affect Consumer Purchase Decisions On Cimory Product - Lukman Norhakim Panji Mandiri; Jamhari Jamhari; Dwidjono Hadi Darwanto (Agro Ekonomi, 2022)
Social media influencers are the ones who become famous for their skills. As a result, influencers have many followers. Influencer credibility impacts consumers` willingness to shop for products, such a lot of manufacturers pay influencers to promote their products. Influencers do not influence sales but through several processes such as increasing brand awareness, brand image, and is expected to trigger word of mouth marketing among consumers. These three expectations are expected to influence consumers in their purchasing decisions. This study examines how an influencer can influence brand awareness, brand image, and word of mouth, which can influence consumer purchasing decisions. This study involved 300 respondents who filled out the questionnaire boldly, then SEM analysis was carried out using AMOS. The results of the study found that influencers can have a positive effect on word of mouth, brand awareness, brand image and consumer purchasing decisions. These results show that influencer role in this digital era have important role and must be properly implemented with influencer use in order to have a positive impact on the brand.